Effect of surfactauts on gas hold-up in baffed column reactor - Jabir, Atheel Khairi (Journal of Petroleum Research and Studies, 2013)
The present work aims to study the performance of Baffled bubble Column Reactor on homogeneous flow regime .Experiments were carried out to investigate the effect a surface active agent (type and concentration ) on Gas Hold-Up in Baffled bubble Column Reactor on with the border range of superficial gas velocity (0.001 -0.039 m/s). Ethanol and hexanol were used as surfactants in the present work. Also three types of baffles: perforated, circular and fin baffle were used. The results show that the gas hold up increases with increasing the concentration of the surfactants. The highest values of gas hold up were recorded in the presence of perforated baffle with 30% of ethanol-water and hexanol-water mixture.